Determination of cannabinoids in hair: Indicators for illegal vs CBD-rich cannabis use. (April 2022) - Casati, Sara; Angeli, Ilaria; Bergamaschi, Roberta F.; Ravelli, Alessandro; Colombo, Gaia; Binelli, Giorgio; Minoli, Mauro; Orioli, Marica
Highlights: Hair samples of CBD-rich cannabis users present THC metabolites with unusual profiles. Preliminary parameters are proposed for differentiating CBD-rich cannabis use. CBD/THC does not differ between CBD-rich cannabis users and hemp inflorescences. Abstract: Cannabis products rich in cannabidiol (CBD) and low in Δ9-tetrahydrocannabinol (THC) (e.g., light cannabis in Italy) are becoming widely popular and available on the market as replacements for THC preparations and tobacco for their recreational and/or therapeutic benefits. In this paper, which aims to establish alternative discrimination parameters between hair samples from CBD-rich and THC-prevalent cannabis users, cannabinoid concentrations, such as THC, CBD, 11-nor-9-carboxy-Δ9-tetrahydrocannabinol (THC-COOH) and 11-hydroxy-Δ9-tetrahydrocannabinol (11-OH-THC) were quantified in 127 hair samples by a GC-MS/MS technique. Initially, this analysis was able to discriminate two cohorts: cohort 1 (individuals with THC values ≥ 0.05 ng/mg and THC-COOH ≥ 0.2 pg/mg or THC-positive users, n  = 60) and cohort 2 (individuals with THC values ranging between 0.01 and 0.05 ng/mg and THC-COOH or 11-OH-THC ≥ LOQs, n  = 67). The evaluation of CBD/THC ratio in cohort 2 identified two further sub-cohorts 2a (CBD/THC<<1 or ~ 1, THC-prevalent cannabis users) and 2b (CBD/THC>>1, suspected CBD-rich and THC-low cannabis users). The latter showed unusual profiles for THC metabolites, in particular for 11-OH-THC. Statistical evaluation of the data of cohort 1, cohort 2a and cohort 2b yielded significant differences in CBD/THC and THC/11-OH-THC. Based on the analysis of 337 seized cannabis samples and 630 CBD-rich/light cannabis samples by GC-FID and GC-MS, respectively, we also evaluated statistical differences in the CBD/THC ratio between biological (hair) and plant-derived samples. Considering the legal implications of a positive result, the obtained findings could be relevant for the interpretation of cannabinoid concentrations in hair. Further studies are necessary to elucidate the reason behind the unusual metabolic ratios.